2015
DOI: 10.1523/jneurosci.0317-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Functional Deficiencies in Fragile X Neurons Derived from Human Embryonic Stem Cells

Abstract: Fragile X syndrome (FXS), the most common form of inherited mental retardation, is a neurodevelopmental disorder caused by silencing of the FMR1 gene, which in FXS becomes inactivated during human embryonic development. We have shown recently that this process is recapitulated by in vitro neural differentiation of FX human embryonic stem cells (FX-hESCs), derived from FXS blastocysts. In the present study, we analyzed morphological and functional properties of neurons generated from FX-hESCs. Human FX neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
58
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 48 publications
13
58
3
Order By: Relevance
“…These observations point to the importance of repeat length in epigenetic silencing of FMRP and highlight the need to consider somatic mosaicism (or repeat instability) along with the need to characterize multiple clones from subjects if single cell clones are selected 16 . Importantly in terms of replication of findings in different FMR1 mutation lines, similar neurodevelopmental deficits have been reported in both human embryonic stem cell (hESC) models 12,13 and in other iPSC models 15 . Taken together, these results suggest the possibility that adult neurogenesis pathways are dysregulated in Fragile X syndrome patients.…”
Section: Phenotypic Assays In Human Ipsc Models Of Neuropsychiatrisupporting
confidence: 56%
See 1 more Smart Citation
“…These observations point to the importance of repeat length in epigenetic silencing of FMRP and highlight the need to consider somatic mosaicism (or repeat instability) along with the need to characterize multiple clones from subjects if single cell clones are selected 16 . Importantly in terms of replication of findings in different FMR1 mutation lines, similar neurodevelopmental deficits have been reported in both human embryonic stem cell (hESC) models 12,13 and in other iPSC models 15 . Taken together, these results suggest the possibility that adult neurogenesis pathways are dysregulated in Fragile X syndrome patients.…”
Section: Phenotypic Assays In Human Ipsc Models Of Neuropsychiatrisupporting
confidence: 56%
“…Despite the known relationship between the CGG-repeat expansion in the 5’ untranslated region of the Fragile X Mental Retardation 1 gene ( FMR1 ) that leads to FMR1 silencing and the loss of expression of the Fragile X Mental Retardation Protein (FMRP), the consequences of the loss of FMRP still remain poorly understood 10 . As reviewed in more detail by Bhattacharyya and Zhao in this special issue 11 , multiple human embryonic stem cell (hESC) 12,13 and in iPSC models of Fragile X syndrome have now been generated 14,15 . For example, Sheridan et al 14 reported on the characterization of iPSC models of Fragile X syndrome from multiple subjects with CGG repeat sizes in the full mutation range (>200), and demonstrated that the FMR1 locus remained epigenetically silenced in iPSC-derived CNS neural progenitor cells and neurons.…”
Section: Phenotypic Assays In Human Ipsc Models Of Neuropsychiatrimentioning
confidence: 99%
“…In addition to high incidence of epilepsy [150,151] and increased head circumference that may be present in FXS patients [152,153], consistent neuronal pathology includes increased dendritic spine density and overabundance of immature-shaped spines on neurons in various brain regions [154,155], which are thought to affect synaptic plasticity and network function (Table 1). In addition, it was shown that in vitro neurons derived from human FXS pluripotent stem cell lines show reduced cell size and neurite length [156,157,158] (Table 1). Accordingly, Fmr1 KO mice, a model for human FXS, also exhibit a seizure phenotype [159,160], neurons with shorter neurite length [161] and with the atypical immature feature of FXS spines [160,162,163,164,165,166].…”
Section: Mtorc1 Signaling Pathway In Monogenic Autism Spectrum Dismentioning
confidence: 99%
“…Among these latter brain abnormalities, increased mGluR-LTD and protein synthesis were proved to play an important role in the neurological manifestations of FXS. In addition, less consistent results exist regarding decreased/normal neurite arborization in neurons derived from human FXS pluripotent stem cell lines [157,158], as well as normal/increased neuron size [175,176], increased/decreased/normal dendritic spine density [160,162,163,164,175,177] or length [165,175,178] and decreased/increased LTP [179,180,181] in Fmr1 KO mice (Table 1). These discrepancies have been suggested to be due to differences in experimental conditions, brain regions examined, age and genetic background of the animals.…”
Section: Mtorc1 Signaling Pathway In Monogenic Autism Spectrum Dismentioning
confidence: 99%
“…These studies led to conflicting results, encouraging scientists to generate disease animal models to monitor the developmental regulated processes in FXS embryos. Both knockout and transgenic knockin mouse models for FXS have been created [15,16,18,20,22], but although FMR1 knockout mice have been extremely informative for studying the clinical pathology of FMRP deficiency, they fail to recapitulate the course of the disease in a developmentally regulated context because they are FMRP protein deficient from day 1 [108]. On the other hand, when a human transgene of CGGs (PM range) was targeted into the 5′-UTR of FMR1 by homologous recombination, the PM rarely expanded into the full mutation range in the offspring, and when it did, it often contracted and manifested almost no aberrant methylation, leaving the FMR1 gene active [23].…”
Section: Neurological Pathology In Fxs Neurons Derived From Hpscmentioning
confidence: 99%